A percepção dos sons vocálicos em Aristóteles - Tulio Cardoso Rebehy (2009)
The perception of spoken sounds is a trouble to Aristotles theory of perception, because perception, strictly speaking, is of perceptibles by itself: the eye sees color, the ear hears sound. As the voice is not only a sound, since it is a sound that can mean, it can not be perceived by itself, but only by accident. Therefore, if the meaning needs intellection and the animals do not have such capacity, how would they perceive sound and understand meaning?